ANALISIS EKSPOR SEKTOR PERTANIAN DAN INDUSTRI PENGOLAHAN TERHADAP PERTUMBUHAN EKONOMI PROVINSI DI PULAU SUMATRA - Febriyanti, Kharisma; Achmad, Erni; Nurjanah, Rahma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to examine the development of exports in the agricultural sector and the processing industry, as well as to examine the contribution of the export value of the two sectors to the economic growth of the provinces on Sumatra Island throughout the year 2019-2024. The data used in this study is secondary data in the form of panel data sourced from the Central Statistics Agency (BPS), covering 10 provinces in Sumatra Island during the 2019-2024 period. The analysis methods applied in this study include descriptive analysis and panel data regression analysis with the Fixed Effect Model (FEM) approach which is selected based on the results of the Chow test and the Hausman test. The research findings show that the export development of the agricultural sector and the processing industry throughout the period of observing fluctuating and uneven patterns between provinces. The results of the panel data regression estimation show that the export of the agricultural sector has a positive but not significant influence on economic growth, while the export of the processing industry sector has a positive and significant effect on economic growth. Simultaneously, both variables have a significant effect on economic growth.